The Role of User Generated Content on Purchase Intention with Mediation of Perceived Usefulness and Perceived Trust - Zakaria, Diyas Luthfi; Maulana, Daniel; Agustina (Indonesian Journal of Advanced Research, 2024)
The focus of this research is to ascertain how the material created by the user, through the perception of usability and the perception of trust, influences the purchase intent. Purposive sampling is the strategy used in this qualitative research. 154 people who use social media and search for user-generated content (UGC) to find information about a product. The data analysis of this study was carried out using SmartPLS 4.0. The results of the hypothesis show that the p-value of each relationship between variables has a value below 0.05. The findings show that there is an influence of user-generated content on purchase intention. The perceived usefulness and perceived trust variations are also able to mediate the relationship between user-generated content and purchase intent.